2020
DOI: 10.3390/ma13102369
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Cell-Free Collagen Type I-Based Scaffold for Articular Cartilage Regeneration in an Orthotopic Rat Model

Abstract: The management of chondral defects represents a big challenge because of the limited self-healing capacity of cartilage. Many approaches in this field obtained partial satisfactory results. Cartilage tissue engineering, combining innovative scaffolds and stem cells from different sources, emerges as a promising strategy for cartilage regeneration. The aim of this study was to evaluate the capability of a cell-free collagen I-based scaffold to promote cartilaginous repair after orthotopic implantation in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Therefore, microfracture augments, which are often placed in the cartilage lesion after the subchondral bone has been repeatedly punctured, have received increased interest in terms of improving outcomes. One such addition to the microfracture regimen being explored is the collagen scaffold—even without microfracture, animal models of cartilage lesions repaired with highly porous collagen I scaffolds showed improved regeneration of cartilage tissue compared to controls [ 19 ]. In this application, a collagen scaffold that would fill the hole formed by missing cartilage would be placed on top of the bone that has been punctured by the microfracture procedure.…”
Section: Collagen Scaffoldsmentioning
confidence: 99%
“…Therefore, microfracture augments, which are often placed in the cartilage lesion after the subchondral bone has been repeatedly punctured, have received increased interest in terms of improving outcomes. One such addition to the microfracture regimen being explored is the collagen scaffold—even without microfracture, animal models of cartilage lesions repaired with highly porous collagen I scaffolds showed improved regeneration of cartilage tissue compared to controls [ 19 ]. In this application, a collagen scaffold that would fill the hole formed by missing cartilage would be placed on top of the bone that has been punctured by the microfracture procedure.…”
Section: Collagen Scaffoldsmentioning
confidence: 99%
“…Undoubtedly, an ideal scaffold material for dentine–pulp complex regeneration needs to have good biocompatibility, controllable biodegradability, suitable mechanical property and porosity, good surface adhesion property, etc [ 3 ]. As a main component of extracellular matrix, type I collagen plays important roles in bone, cartilage, skin, vessel, nerve and ligament regeneration due to its superior biocompatibility, low immunogenicity and suitable biodegradation properties [ 4–6 ]. Several studies have shown that type I collagen is one of the most ideal scaffold materials for dental pulp regeneration [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these processes require an initial step of primary cell expansion. Regenerative medicine typically uses patient's autologous cells, seeds them on suitable support materials, induces cell differentiation through the addition of specific growth factors and then uses the matured construct or the cell secretome to induce healing or for a total replacement of the tissue 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%